Amelioration of AOM/DSS-Induced Murine Colitis-Associated Cancer by Evodiamine Intervention is Primarily Associated with Gut Microbiota-Metabolism-Inflammatory Signaling Axis - Wang, Mengxia; Zhou, Biqiang; Cong, Weihong; Zhang, Miao; Li, Ziwen; Li, Yan; Liang, Shaoyu; Chen, Keji; Yang, Depo; Wu, Zhengzhi (Frontiers in Pharmacology, 2021)
Evodiamine (EVO), an indole alkaloid derived from Rutaceae plants Evodia rutaecarpa (Juss.) Benth.、Evodia rutaecarpa (Juss.) Benth. Var. bodinieri (Dode) Huang or Evodia rutaecarpa (Juss.) Benth. Var. officinalis (Dode) Huang, has anti-inflammatory and anti-tumor activities. Our previous study found that EVO attenuates colitis by regulating gut microbiota and metabolites. However, little is known about its effect on colitis-associated cancer (CAC). In this study, the protective effects of EVO on azoxymethane (AOM)/dextran sulfate sodium (DSS)-induced colitis and tumor mice were observed, and the underlying potential mechanism was clarified. The results suggested that EVO ameliorated AOM/DSS-induced colitis by inhibiting the intestinal inflammation and improving mucosal barrier function. And EVO significantly reduced the number and size of AOM/DSS-induced colorectal tumors along with promoted apoptosis and inhibited proliferation of epithelial cell. Moreover, EVO promoted the enrichment of SCFAs-producing bacteria and reduced the levels of the pro-inflammatory bacteria, which contributes to the changes of microbiota metabolism, especially tryptophan metabolism. Furthermore, inflammatory response (like Wnt signaling pathway、Hippo signaling pathway and IL-17 signaling pathway) were effectively alleviated by EVO. Our study demonstrated that the protective therapeutic action of EVO on CAC is to inhibit the development of intestinal inflammation-cancer by regulating gut microbiota metabolites and signaling pathways of colon intestinal epithelial, which may represent a novel agent for colon cancer prevention via manipulation of gut microbiota.